Online Learning during the Pandemic: Analyzing Academic Motivation among Culture and Arts Students - Christine H. Pesidas; Juspher G. Handang; Kathleen A. Gregorio; Nurfaiza J. Joe (Researchparks Publishing, 2022)
This study discusses the problem or the impact of learning Culture and Arts during this time of the pandemic. Learning culture and arts online is believed to be a real problem in the students’ academic motivation. The aim of this study was to analyze the academic motivation of culture and arts students during pandemic. There are studies that have been conducted about the motivation of learning arts online, however, previous studies appeared to only surveyed students with specialties in arts, music, and dance. A total of 100 Culture and Arts undergraduates of Western Mindanao State University and other university offering Bachelor of Culture and Arts Education course participated in the present study. Independent-samples T-test, descriptive statistics, and one-way ANOVA were used to code and analyze the data in this study. Result shows that, due to the widespread occurrences brought by the pandemic, learning culture and arts in a pandemic learning context, the respondents have no strong marked or positive academic motivation. In terms of difficulties, the results stated that the students are also doing all the works to be motivated in learning culture and arts during pandemic/online learning. It was also concluded that there is no significant difference on the Academic Motivation on Learning Culture and Arts during Pandemic in terms of gender.